2011
DOI: 10.1063/1.3672515
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and energy scaling of quasi-monoenergetic protons in laser radiation pressure acceleration

Abstract: Theoretical and computational studies of the ion energy scaling of the radiation pressure acceleration of an ultra-thin foil by short pulse intense laser irradiation are presented. To obtain a quasi-monoenergetic ion beam with an energy spread of less than 20%, two-dimensional particle-in-cell simulations show that the maximum energy of the quasi-monoenergetic ion beam is limited by self-induced transparency at the density minima caused by the Rayleigh-Taylor instability. For foils of optimal thickness, the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…17 This is a more efficient acceleration process for producing high energy monoenergetic protons, suitable for many applications requiring that the accelerated protons have good beam quality and a narrow energy spectrum. However, previous works demonstrated with two-dimensional (2D) particle-in-cell (PIC) simulations 16,18,[22][23][24] that the Rayleigh-Taylor instability (RTI) limits the acceleration achieved by RPA and rapidly broadens the proton beam's energy spectrum. For RPA of thin-foil targets of one species, the energy scaling study with PIC simulation 18 indicates that petawatt power laser is needed to obtain $200 MeV quasi-monoenergetic protons with energy spread within 20% of the peak flux energy, which may make the laser proton acceleration scheme less attractive for commercial practical applications, as it is difficult to build a petawatt laser, and the laser also produces strong radiation that is difficult to shield.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 This is a more efficient acceleration process for producing high energy monoenergetic protons, suitable for many applications requiring that the accelerated protons have good beam quality and a narrow energy spectrum. However, previous works demonstrated with two-dimensional (2D) particle-in-cell (PIC) simulations 16,18,[22][23][24] that the Rayleigh-Taylor instability (RTI) limits the acceleration achieved by RPA and rapidly broadens the proton beam's energy spectrum. For RPA of thin-foil targets of one species, the energy scaling study with PIC simulation 18 indicates that petawatt power laser is needed to obtain $200 MeV quasi-monoenergetic protons with energy spread within 20% of the peak flux energy, which may make the laser proton acceleration scheme less attractive for commercial practical applications, as it is difficult to build a petawatt laser, and the laser also produces strong radiation that is difficult to shield.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous works demonstrated with two-dimensional (2D) particle-in-cell (PIC) simulations 16,18,[22][23][24] that the Rayleigh-Taylor instability (RTI) limits the acceleration achieved by RPA and rapidly broadens the proton beam's energy spectrum. For RPA of thin-foil targets of one species, the energy scaling study with PIC simulation 18 indicates that petawatt power laser is needed to obtain $200 MeV quasi-monoenergetic protons with energy spread within 20% of the peak flux energy, which may make the laser proton acceleration scheme less attractive for commercial practical applications, as it is difficult to build a petawatt laser, and the laser also produces strong radiation that is difficult to shield. 25,26 However, by using a thin composite multi-ion protoncarbon foil, researches have shown that the energy can be further increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to acquire quasi-monoenergetic protons, the scheme of laser RPA has been actively studied in theory and simulations [18][19][20][21][22][23][24][25][26] and experiments. 27,28 In RPA, a high intensity circularly polarized laser beam irradiates an ultra-thin foil and accelerates nearly the whole foil by the radiation pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Protons with quasi-monoenergy and high beam quality were obtained in simulations. [13][14][15][16][17][18][19][20][21] However, solid hydrogen targets are difficult to produce in experiment and only diamond-like carbon has been used experimentally with limited success. 15 Recently, CO 2 laser proton acceleration with gas targets has attracted much interest since hydrogen gas is readily available, and CO 2 laser is low-cost, long-duration and able to deliver substantial amounts of energy.…”
Section: Introductionmentioning
confidence: 99%